First confirmed species record of Hydroscaphidae from Peru: description of a new species of Yara Reichardt and Hinton, and key to species (Coleoptera: Hydroscaphidae) - Trujillo, Gabriel A.; Cañote, Javier (Zootaxa, 2019)
The Hydroscaphidae (“skiff beetles”) is a family of minute aquatic beetles within the suborder Myxophaga comprising four genera: Hydroscapha Le Conte, 1874; Scaphydra Reichardt, 1973; Yara Reichardt & Hinton, 1976 and Confossa Short et al., 2015. All genera are found within the Neotropical region, with the exception of Hydroscapha, which is widespread. Representatives of this family have been reported for Venezuela, Brazil, Panama (Short et al. 2015) and Nicaragua (Raudez et al. 2019).